Vespasian and Mettius Pompusianus - Woods, David (Classica et Mediaevalia, 2022)
Several ancient sources agree that the emperor Vespasian did not punish a certain Mettius Pompusianus when he learned that he had received an imperial horo- scope, but appointed him as consul. It is argued here that Vespasian intended his appointment of Pompusianus as consul as the fulfilment of this horoscope which was vaguer in its original language than the surviving sources suggest. This saved him from having to punish Pompusianus.